COVID 19 in phase 2 sustained. Initial surgical experience at the Maciel Hospital - Ruso Martínez, Luis; Rodríguez Temesio, Gustavo; Perdomo, Mauro; Olivera Pertusso, Eduardo; Bruno, Gerardo; González González, Daniel; Rodríguez, María Ángeles; Camejo, Eduardo; Crestanello, José; Charlone, Rogelio; Fernández Casas, Ricardo; Mouro, Laura; et al. (Cirugía del Uruguay, 2020)
Introduction. In Uruguay, the start of the pandemic was decreed by Covid. 19 on March 13, 2020, In this context, the Maciel Hospital (HM) established guidelines and recommendations to face the disease that radically modified its usual benefits. The objective of this communication is to present the surgical experience developed in the care context of a sustained phase 2 of Covid infection.19 Material and methods The surgical activity of the HM is retrospectively analyzed from its record of Operative Descriptions, during the period between 13.3.2020 and 30.4.2020 (49 days) and performs a critical analysis from the governing documents of our surgical conduct. Results: 403 cases, 149 coordination and 254 emergency were operated. 287 patients with multiple etiologies, although predominantly oncological (27%) and infectious / inflammatory processes (19%), were operated by the general and specialty surgery services. Laparoscopy involved 62 cases, 43 of which were urgent, mostly due to infectious / inflammatory pathologies: appendicitis (35%), cholecystectomies (24%), and diagnostic laparoscopies (11%). 55% of the cases underwent surgery for cancer and the rest cholecystectomies and others. Conclusions: The HM operated three times more than the rest of the public system; Even so, with respect to its usual production, the number of surgeries decreased significantly (35%), especially coordination (59%). Covid.19 positive patients were not operated. A high number of justified operations were carried out in terms of quantity and type of pathology, using the protocol for maximum protection against Covid.19 rationally, within the established sanitary guidelines and without infectious impact by the coronavirus